PETA RUJUKAN AL-QATTAN: ANALISIS KRITIS SUMBER HADIS DAN ULUMUL QUR’AN - Farhan Abdillah (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
This study aims to analyse Manna Khalil al-Qattan's reference map in the chapter on Qira'at in the book Mabahith fi 'Ulum al-Qur'an, with a focus on mapping the sources of hadith and ulumul Qur'an used. Al-Qattan, a leading scholar in the field of Ulumul Qur'an, integrates hadith sources and classical works of ulumul Qur'an to explore aspects such as qira'at and ahruf sab'ah. This book relies on authentic hadiths from Imam al-Bukhari and Imam Muslim, as well as influential works of ulumul Qur'an, such as Al-Itqan by Jalaluddin as-Suyuti and Al-Burhan by al-Zarkasyi, to strengthen his arguments. The results of the study show that Al-Qattan preferred authentic and sahih sources in constructing his analysis, with a tendency to avoid more modern secondary sources. This approach reflects a conservative methodology based on authenticity and accuracy, making Mabahith fi 'Ulum al-Qur'an an important reference in scientific studies of the Qur'an. This research also shows Al-Qattan's important contribution in revitalising the understanding of qira'at and standardising the recitation of the Qur'an through an approach based on valid sources.